THE EFFECT OF ANNEALING AND COLD FORGING ON MICROSTRUCTURE AND HARDNESS PROPERTIES OF Al-SiC COMPOSITE : A PRELIMINARY STUDY - Adityawardhana, Yudhistira; Zulfia, Anne; Adjiantoro, Bintang; Hasbi, Muhammad Yunan (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
Aluminum Metal Matrix Composites (AMMCs) are among the exciting materials that have an extensive function in various applications. Reinforcement in the fabrication process of Al composites can produce superior properties such as high strength, good fracture resistance, and of course, lightweight. Therefore, many studies are interested in revealing the characteristics of Al composite materials through various methods and variations of reinforcement. This research was a preliminary study with a scope of work that includes observation on the effects of annealing and cold forging processes on microstructure morphology and hardness properties of SiC nano-ceramic reinforced of Al composites. The aluminum used in this study was a 7xxx series aluminum alloy. The fabrication process was carried out by stir-squeeze casting method. Microstructure analysis was conducted by optical microscopy and Scanning Electron Microscopy (SEM) equipped with Emission Dispersion Spectroscopy (EDS). The hardness properties of the Al-SiC composite were examined by micro-Vickers hardness testing. This paper reports that annealing process influences grain refinement and hardness properties of the Al-SiC composite. The sample experiencing cold forging shows improvement in the hardness value. Increase of hardness value by forging after annealing may be promoted due to grain compression as dislocation mechanism effect. Comprehensive research is required to discover other potentials of Al-SiC composite materials.